Relationships between Agency-Specific Contact, Victimization Type, and Trust and Confidence in the Police and Courts - Berthelot, Emily R. (American journal of criminal justice, 2018)
While the extant research on trust and confidence in the criminal justice system is broad in scope, its individual studies are more limited, leaving much unknown about these relationships. Building on prior research, the current study investigates the relationships between prior contact, victimization, and seven measures of trust and confidence in the police and courts. This study responds to calls for the relationships between trust and confidence in the criminal justice system, race/ethnicity, prior contact, and victimization to be investigated within a single study. Although rare in prior research, outcomes of trust and confidence in local police and courts are individually investigated within the same sample simultaneously. As a first, the current study also separates prior contact by police, courts, community corrections, and institutional corrections and examines four types of victimization (direct violent, vicarious violent, direct non-violent, vicarious non-violent). The latter allows for an examination of potentially more nuanced relationships between victimization and trust and confidence in the police and in the courts.